Contribution To Optimize Induction Machines Performance Using New Magnetic Material - Salah Ellddine BOUTASSOUNA; Mohammed Yacine DJERFAFــــــــ; Tahar SEGHIERE (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2022)
In this research, we are interested in studying the induction motor, where we aspire to improve the way, it works by changing its materials with other new materials. Which in turn contributes to raising the efficiency of the induction motor in several ways. In order to Modulate and simulate, we used the COMSOL-MultiPhysics Software. This program studies physical phenomena such as mechanical force and magnetic saturation in solid media.
Option : Industrial electrical engineering .